Code Division Multiple Access (CDMA) using direct sequence spread spectrum technique / Redzwan Rosli - Rosli, Redzwan (2007)
The purpose of this project is to investigate the Code Division Multiple Access (CDMA) communications using Direct Sequence Spread Spectrum (DS-SS). Spread Spectrum Communication techniques have been widely accepted in mobile and wireless communications especially in Code Division Multiple Access (CDMA). CDMA has very beneficial and tempting features, like Anti jam, security, and Multiple Access. It is the purpose of this paper to describe the features of Spread Spectrum systems. The emphasis will be on the Direct Sequence Spread Spectrum (DS-SS) scheme, Pseudo Noise signals (PN), Modulators and Demodulators, and finally a MATLAB simulation is used to illustrate some of the DS-SS system features. The result that were obtained through these analysis showed that the precise and accurate of any system can be achieved by simulation software, therefore MATLAB is chosen in designing, simulating, testing and analyzing the system. Focus will be given to Pseudo noise (PN) signal. Pseudo Noise (PN) signals are the key factor in DS-SS systems. They are the ones responsible for the spreading and de spreading of the base band signal.